2021
DOI: 10.20901/pm.58.2.07
|View full text |Cite
|
Sign up to set email alerts
|

The image of geolocations in a virtual environment

Abstract: The main framework of this interdisciplinary research interconnects the cyclic‎ process of space creation in a virtual environment, including the various perspectives‎ in social sciences. Combining media, communication, popular geopolitics,‎ PR and big data this paper introduces a model for testing and evaluating‎ the importance of transaction data on image analysis of geolocations in‎ tourism, as well as the importance of shown interest for different destinations.‎ The data is gathered through the Google Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Borderlands research in Southeast Europe (e.g., in Serbia and Croatia) has applied a range of methodological approaches to confirm the hypothesis of border regions as economically, socially and demographically marginalized parts of the national territory (Popović and Radeljak 2011;Zorko 2012;Pejnović and Kordej-De Villa 2015;Vukmirović et al 2016). In comparing the socio-economic indicators of border regions with the national average and examining the standard of living in these areas (Máliková et al 2015;Đerčan et al 2016), determining the incidence of demographic issues (Zupanc 2018;Anđelković-Stoilković 2019) and analyzing borderlands in the context of national security (Vukmirović et al 2016), multiple authors have concluded that border regions are observed through the paradigm of spatial polarization due to the disparity in the levels of development between the center and periphery.…”
Section: Introductionmentioning
confidence: 99%
“…Borderlands research in Southeast Europe (e.g., in Serbia and Croatia) has applied a range of methodological approaches to confirm the hypothesis of border regions as economically, socially and demographically marginalized parts of the national territory (Popović and Radeljak 2011;Zorko 2012;Pejnović and Kordej-De Villa 2015;Vukmirović et al 2016). In comparing the socio-economic indicators of border regions with the national average and examining the standard of living in these areas (Máliková et al 2015;Đerčan et al 2016), determining the incidence of demographic issues (Zupanc 2018;Anđelković-Stoilković 2019) and analyzing borderlands in the context of national security (Vukmirović et al 2016), multiple authors have concluded that border regions are observed through the paradigm of spatial polarization due to the disparity in the levels of development between the center and periphery.…”
Section: Introductionmentioning
confidence: 99%